2017
DOI: 10.1016/j.plgene.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic acid causes short- and long-term alterations to the transcriptome and the expression of defense genes in sugarbeet roots

Abstract: Jasmonic acid (JA) induces native defense responses in plants and increases the resistance of postharvest sugarbeet roots to three common storage-rot causing organisms. To gain insight into the defense responses induced by JA in harvested sugarbeet roots, RNA was isolated from roots treated with water or 10 µM JA and incubated for 2 or 60 d post-treatment. RNA was sequenced, and sequence data was analyzed for short-term (2 d) and long-term (60 d) effects of JA on the sugarbeet root transcriptome. A total of 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…JA application inhibited postharvest pathogens in fruit such as loquats, sugarbeet roots (Beta vulgaris), grapes, peaches, and apricots (Cao et al, 2008;Fugate et al, 2012;Nimitkeatkai et al, 2011;Wang et al, 2015a;Yao and Tian, 2005). Fugate et al (2017) found that MeJA application upregulated genes for PR proteins as a defense response in sugar beet roots. In our study, the JA concentrations increased in the PDJ + Ino + group, whilst the expression levels of MdAOS1 also increased.…”
Section: Discussionmentioning
confidence: 99%
“…JA application inhibited postharvest pathogens in fruit such as loquats, sugarbeet roots (Beta vulgaris), grapes, peaches, and apricots (Cao et al, 2008;Fugate et al, 2012;Nimitkeatkai et al, 2011;Wang et al, 2015a;Yao and Tian, 2005). Fugate et al (2017) found that MeJA application upregulated genes for PR proteins as a defense response in sugar beet roots. In our study, the JA concentrations increased in the PDJ + Ino + group, whilst the expression levels of MdAOS1 also increased.…”
Section: Discussionmentioning
confidence: 99%
“…JA signaling have been linked to the alteration of plant secondary metabolites, including alkaloids, terpenoids, flavonoids, phenolic compounds, and phytoalexins (7579). Secondary metabolites derived from multiple branches of the phenylpropanoid pathway, including lignins, isoflavonoid-phytoalexins, and other phenolic compounds have also been proposed as important components of defense responses (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The phytohormone MeJA has been characterized as a vital cellular regulator involved in a number of dynamic processes, linked to the development of active responses in the defence against biotic and abiotic stresses . It is also active in processes closely linked to oxidative stress, regulating the activity of antioxidant enzymes …”
Section: The Jasmonates Family and Methyl Jasmonatementioning
confidence: 99%
“…[30] The phytohormone MeJA has been characterized as a vital cellular regulator involved in a number of dynamic processes, linked to the development of active responses in the defence against biotic and abiotic stresses. [31,42] It is also active in processes closely linked to oxidative stress, regulating the activity of antioxidant enzymes. [43] Some plants contain relatively high levels of circulating MeJA: the olive tree, species of the Jasminum genus, the orchid Cymbidium goeringii, the tuberose (Polianthes tuberosa), Chloranthus spicatus, Ginger, Boronia megastigma, honeysuckle (Lonicera japonica), Artemisia tridentate and rosemary (Rosmarinus officinalis).…”
Section: Pathogenesis Of the Principals Ibds: Clinical Symptoms Inflmentioning
confidence: 99%